Cognitive Skills and Academic Performance in Children With Minimal to Mild Conductive Hearing Loss: The Roles of Listening Effort and Subjective Fatigue. - Jain, Saransh; M. S., Vasantha Lakshmi; S., Sanjana Singh; H. S., Harshan Kumar; Jain, Chandni (American Journal of Audiology, 2026)
Purpose: This study examined how cognitive skills (nonverbal intelligence, verbal working memory, and attention) influence academic performance in children with minimal to mild conductive hearing loss (mCHL) and whether this relationship is moderated by subjective fatigue and listening effort. We also compared these effects with age- and sex-matched children with normal hearing sensitivity (NHS). Method: A cross-sectional correlational study was conducted on 130 children with mCHL and 130 children with NHS (aged 10-12 years). Audiological testing, cognitive assessments (Seguin form board test, digit span, operation span, and dichotic digit tests), and subjective fatigue ratings (visual analog scale) were collected. Listening effort was measured using a dual-task paradigm that involved speech-in-noise and digit-reversal tasks. Teachers rated academic performance using the Academic Performance Rating Scale and supported by recent academic marks. Multiple linear regression and moderation analyses were performed. Results: Children with mCHL exhibited significantly higher listening effort, greater subjective fatigue, lower cognitive scores, and poorer academic performance than their peers with NHS did. Moderation analysis revealed that subjective fatigue significantly weakened the positive relationship between cognition and academic performance in children with mCHL but not in children with NHS. A z test confirmed that the moderating effect was significantly stronger in the mCHL group. Conclusions: These findings suggest that subjective fatigue plays a critical role in modulating the effects of cognition on academic success in children with mCHL. Interventions addressing listening efforts and fatigue management are suggested for improving educational outcomes in this population. Supplemental Material: https://doi.org/10.23641/asha.31057807